Analysis of Financial Performance of Pt. Bank Muamalat Indonesia for the 2020-2024 Period (Horizontal and Ratio Methods) - Awalia Rizqiani, Hu'shila (Jurnal Hadratul Madaniyah, 2025)
This study aims to analyze the financial performance of PT. Bank Muamalat Indonesia for the 2020–2024 period using horizontal analysis methods and financial ratios. Horizontal analysis is carried out on the balance sheet statement as well as comprehensive income and income statements, while financial ratio analysis refers to the provisions of Bank Indonesia through the CAMEL approach which focuses on capital, asset, earning, and liquidity aspects. The results showed that in terms of balance sheet, total assets and investments in securities experienced a significant increase, while current accounts, savings, deposits, third-party funds, liabilities, equity, and investments in net associated entities showed fluctuating developments. Horizontal analysis of the income statement shows unstable conditions, where the comprehensive profit for the current period increased only in 2022, while in 2021, 2023, and 2024 it actually decreased. Furthermore, the results of the financial ratio analysis show that Bank Muamalat has a capital adequacy ratio (CAR) which is in the very healthy category throughout the research period, as well as good asset quality with a controlled Non-Performing Financing (NPF) level. However, the bank's profitability is still low with a return on asset (ROA) ratio that is in the unhealthy category, as well as the BOPO efficiency ratio which is in the unhealthy category due to high operating expenses. On the other hand, the level of bank liquidity measured through the financing to deposit ratio (FDR) is in the very healthy category, although it shows indications of less than optimal financing distribution. Overall, Bank Muamalat Indonesia has major strengths in terms of capital and liquidity, but still faces serious challenges in increasing profitability and operational efficiency in order to maintain competitiveness in the Islamic banking industry.